ANALISIS WACANA KRITIS MODEL SARA MILLS PADA FILM SEHIDUP SEMATI: REPRESENTASI KETIDAKSETARAAN GENDER - Athaya Salsabila; Mayasari; Tri Widya Budhiharti (KAGANGA KOMUNIKA: Journal of Communication Science, 2026)
This study analyzes gender inequality in the film Till Death Do Us Part by Upi Avianto, which were released in 2024. This psychological thriller genre film raises the issue of gender inequality of the role of wives which leads to domestic violence. Using a qualitative approach with Sara Mills' discourse analysis method, this study uses a descriptive qualitative method combined with Sara Mills discourse analysis as the main analytical framework that aims to understand how the position of gender subjects and objects is constructed in film texts, as well as how the audience is directed to interpret the roles and relationships between men and women. Data was collected through scrutiny of important scenes and dialogues in the film, then analyzed by identifying narrative and visual elements related to gender inequality, as well as the power relations formed between subjects and objects. The results of the study show that this film predominantly represents the wife as an object of helplessness, violence, and fear in the context of an abusive relationship. However, as the narrative progresses, there is a shift in which the wife's character, Renata, slowly transforms from a passive object to an active subject in resisting patriarchal domination and seeking independence.    Keywords: Critical Discourse Analysis of the Sara Mills Model, Gender Inequality Representation, Domestic Violence